A method for manufacturing corrosion-resistant aluminum alloy material for shipbuilding

By coating anticorrosion coatings composed of epoxy resin, corrosion-resistant components and reinforcement components on the surface of the aluminum alloy material, the problems of corrosion of aluminum alloy materials in seawater and poor mechanical properties of the coating are solved, and the effect of improving the corrosion resistance and mechanical properties of aluminum alloy materials is achieved.

CN118580748BActive Publication Date: 2025-03-18SHANDONG XUEDI ALUMINUM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410968386.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-03-18
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

Aluminum alloy materials are prone to corrosion in seawater, and the existing epoxy resin coatings have poor mechanical properties, which are prone to cracking or falling off due to bumps and cracking, losing their protective effect on aluminum alloy materials.

Method used

Anticorrosion coatings composed of epoxy resin, curing agent, corrosion-resistant components and reinforcement components are used to form anticorrosion coatings by stirring evenly, thereby improving the corrosion resistance and mechanical properties of aluminum alloy materials.

Benefits of technology

It significantly improves the corrosion resistance and mechanical properties of aluminum alloy materials, slows down the corrosion rate, enhances the stability and protection effect of the coating, and meets the requirements of ship manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580748B_ABST
    Figure CN118580748B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum alloys, and discloses a method for manufacturing a corrosion-resistant aluminum alloy material for shipbuilding. The corrosion-resistant aluminum alloy material consists of an aluminum alloy substrate and an anticorrosion coating coated on the surface of the aluminum alloy substrate; the anticorrosion coating is formed by curing the anticorrosion coating; the anticorrosion coating comprises the following raw materials in parts by weight: 800-100 parts of epoxy resin, 15-20 parts of curing agent, 3-6 parts of corrosion-resistant components, 5-8 parts of reinforcing components, and 1-3 parts of dispersant. The protective effect of the anticorrosion coating on the aluminum alloy material is achieved by adding the corrosion-resistant component and the reinforcing component to the coating, so that the coating has excellent corrosion resistance and mechanical properties, can protect the aluminum alloy material in a marine environment, slow down the corrosion of the aluminum alloy material by seawater, and at the same time avoid the coating from being cracked or falling off due to collision, thereby reducing the protective effect on the aluminum alloy material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloys, and in particular to a method for manufacturing a corrosion-resistant aluminum alloy material for shipbuilding. Background Art

[0002] Aluminum alloy has good mechanical properties, good corrosion resistance, excellent weldability, plasticity and processing performance. It can be processed into products of various shapes and sizes in a variety of ways. It is recyclable, which is beneficial to environmental protection and resource conservation. The density is much smaller than that of metals such as steel and iron. It is a light metal with excellent lightweight characteristics and can meet lightweight requirements. As a light metal with excellent performance, aluminum alloy is widely used, such as in aerospace, automotive machinery, electronics, construction, shipbuilding, etc. Aluminum alloy is used in ships as key parts of ships. It is exposed to seawater corrosion environment for a long time. Aluminum alloy materials are easily corroded, which will bring safety hazards and property losses to industrial production and transportation; therefore, there are relatively high requirements for the corrosion resistance of aluminum alloy. The corrosion resistance and mechanical strength of the coating can be enhanced by coating the surface of the aluminum alloy, thereby improving the corrosion resistance of the aluminum alloy.

[0003] Epoxy resin has excellent chemical stability, can resist the erosion of chemical substances, has good bonding performance, processing performance and environmental protection. Coating epoxy resin on the surface of aluminum alloy materials can form a protective layer, isolate the external corrosive medium from contacting the aluminum alloy, effectively improve the corrosion resistance of the aluminum alloy materials, make the aluminum alloy materials meet the requirements of shipbuilding, enhance the mechanical properties of the aluminum alloy, and extend the service life of the aluminum alloy materials. In the long run, the use of epoxy resin coatings can reduce the maintenance cost and use cost of aluminum alloys, and have good economic benefits. However, aluminum alloy materials for ships are in a marine corrosive environment for a long time, and the corrosion resistance and mechanical properties of epoxy resin need to be improved to improve the corrosion resistance of the coating, slow down the corrosion rate of the aluminum alloy materials, and at the same time improve the mechanical strength of the coating to avoid bumps that cause the coating to break or fall off, and lose the protective effect on the aluminum alloy materials.

[0004] The patent with publication number CN106280908B discloses an aluminum alloy anti-corrosion coating, its preparation method and application. The invented aluminum alloy anti-corrosion coating is mainly composed of epoxy resin, titanium dioxide, talcum powder, strontium chrome yellow, zinc phosphate, graphene, dispersant, organic solvent, leveling agent, anti-settling agent and epoxy curing agent, etc., and has excellent comprehensive anti-corrosion performance. However, when aluminum alloy is used in shipbuilding, the anti-corrosion coating prepared by this patent ignores the situation that the coating breaks or falls off after collision due to poor mechanical properties of the coating. Therefore, the present invention provides an aluminum alloy material with excellent corrosion resistance after being coated with an anti-corrosion coating, which can be used in shipbuilding and has broad application prospects. Summary of the invention

[0005] The purpose of the present invention is to provide a method for manufacturing a corrosion-resistant aluminum alloy material for shipbuilding, which solves the following problems:

[0006] (1) Solved the problem of aluminum alloy materials being easily corroded in seawater;

[0007] (2) The problem of epoxy resin coating having poor mechanical properties, being easy to crack and fall off after being bumped, and having poor protection for aluminum alloy materials has been solved.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] A corrosion-resistant aluminum alloy material for shipbuilding, comprising an aluminum alloy substrate and an anti-corrosion coating coated on the surface of the aluminum alloy substrate; the anti-corrosion coating is formed by curing the anti-corrosion coating; the anti-corrosion coating comprises the following raw materials in parts by weight: 800-100 parts of epoxy resin, 15-20 parts of curing agent, 3-6 parts of corrosion-resistant components, 5-8 parts of reinforcing components, and 1-3 parts of dispersant.

[0010] Furthermore, the preparation method of the anti-corrosion coating is as follows:

[0011] Put the epoxy resin, corrosion-resistant component, reinforcing component and dispersant into a mixer, set the stirring speed to 600-1200r / min, stir for 2-4h, add the curing agent, stir evenly to obtain the anti-corrosion coating.

[0012] Furthermore, the curing agent is diethylenetriamine or triethylenetetramine; and the dispersant is EFKA5065 or EFKA4010.

[0013] Furthermore, the method for preparing the corrosion-resistant component comprises the following steps:

[0014] Step A, adding hydroxyapatite to dimethyl sulfoxide, stirring until uniformly dispersed, adding 1H-benzimidazole-5-carboxylic acid and p-toluenesulfonic acid, heating to 80-90° C., reacting for 2-3 hours, filtering, washing, and drying to obtain modified hydroxyapatite;

[0015] Step B: adding modified hydroxyapatite and sodium molybdate to deionized water, introducing nitrogen, placing in a magnetic stirrer for stirring, stirring for 6-8 hours, filtering, and drying to obtain a corrosion-resistant component.

[0016] By adopting the above technical scheme, the active hydroxyl groups on the surface of hydroxyapatite can react with the active carboxyl groups in the 1H-benzimidazole-5-carboxylic acid structure under the action of a catalyst to undergo an esterification reaction to obtain modified hydroxyapatite. By utilizing the interlayer structure of the modified hydroxyapatite and the ion exchange capacity of the hydroxyapatite, sodium molybdate is intercalated into the interlayer of the modified hydroxyapatite to obtain a corrosion-resistant component.

[0017] Furthermore, in step A, the particle size of the hydroxyapatite is 5-8 μm.

[0018] Furthermore, the preparation method of the reinforcing component comprises the following steps:

[0019] Step (1), heating the tung oil and formic acid in a water bath to 50-60° C., adding hydrogen peroxide after stirring evenly, reacting for 4-6 hours, standing to separate the water layer, and distilling the oil layer under reduced pressure to obtain epoxidized tung oil;

[0020] Step (2), adding epoxidized tung oil and sodium lignin sulfonate to N,N-dimethylacetamide, stirring evenly, adding boron trifluoride ether complex, heating to 60-70° C., reacting for 3-5 hours, and distilling under reduced pressure to obtain modified sodium lignin sulfonate;

[0021] Step (3), adding modified sodium lignin sulfonate to deionized water, stirring evenly, introducing nitrogen, adding 3-chloropropylamine hydrochloride and triethylamine, heating to 55-65° C., adjusting the pH value, reacting for 4-6 hours, and distilling under reduced pressure to obtain a strengthening component.

[0022] By adopting the above technical scheme, the epoxy groups in the epoxidized tung oil and the active hydroxyl groups in the structure of sodium lignin sulfonate are used to undergo a ring-opening reaction under the action of a catalyst to obtain modified sodium lignin sulfonate. A large number of active hydroxyl groups in the modified sodium lignin sulfonate can undergo a substitution reaction with the chlorine substituent in 3-chloropropylamine hydrochloride, so that amino groups are introduced into the modified sodium lignin sulfonate to obtain a reinforcing component.

[0023] Furthermore, in step (1), the mass fraction of the hydrogen peroxide is 25-30%.

[0024] Furthermore, in step (3), the pH value is 10-10.5.

[0025] A method for manufacturing a corrosion-resistant aluminum alloy material for shipbuilding is as follows:

[0026] After the aluminum alloy substrate is polished, cleaned and dried, the anti-corrosion coating is evenly coated on the surface of the aluminum alloy substrate, and after drying and curing at 100-120° C. for 1-2 hours, an anti-corrosion coating is formed to obtain a corrosion-resistant aluminum alloy material.

[0027] Furthermore, the anti-corrosion coating has a thickness of 15-25 μm.

[0028] Beneficial effects of the present invention:

[0029] (1) The corrosion-resistant component prepared by the present invention contains an imidazole corrosion inhibitor having an electron-donating group benzene ring, which can improve the adsorption performance on the surface of the aluminum alloy substrate and form a molecular film on the metal surface to protect the aluminum alloy substrate and prevent the corrosive environment from contacting the aluminum alloy substrate, thereby achieving the purpose of slowing down and inhibiting corrosion. The sodium molybdate in the corrosion-resistant component is intercalated into the hydroxyapatite interlayer, which can give play to the ion exchange advantage of hydroxyapatite and effectively reduce the concentration of anions in the environment. The sodium molybdate is released through anion exchange and the corrosive anions in the environment are captured, thereby effectively protecting the aluminum alloy substrate. The corrosion-resistant component is added to the coating to improve the corrosion resistance of the aluminum alloy substrate so that it meets the requirements of shipbuilding.

[0030] (2) The reinforcing component prepared by the present invention contains sodium lignin sulfonate, which has a flexible aromatic ring and can improve the mechanical properties of the coating. Castanopsis oil is a natural oil with good wettability and dispersibility, and the long carbon chain structure increases the impact resistance of the coating. After the modified sodium lignin sulfonate reacts with 3-chloropropylamine hydrochloride, it has an amino group and can participate in the curing of the coating to form a more uniform and tight network structure, increase the cross-linking density, and improve the overall mechanical properties of the anti-corrosion coating, so that the anti-corrosion coating will not break or fall off due to bumps and lose its protective effect on the aluminum alloy substrate.

[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 is an infrared spectrum of the modified hydroxyapatite prepared in the embodiment of the present invention;

[0034] Figure 2 This is an infrared spectrum of the modified sodium lignin sulfonate and the strengthening component in the embodiment of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0036] 1. Preparation of corrosion-resistant components

[0037] Step A, adding 3 g of hydroxyapatite with a particle size of 5 μm to dimethyl sulfoxide, stirring until uniformly dispersed, adding 2.5 g of 1H-benzimidazole-5-carboxylic acid and 0.5 g of p-toluenesulfonic acid, heating to 85° C., reacting for 3 h, filtering, washing, and drying to obtain modified hydroxyapatite;

[0038] Step B: Add 2.4 g of modified hydroxyapatite and 5 g of sodium molybdate into deionized water, introduce nitrogen, place in a magnetic stirrer and stir for 8 h, filter and dry to obtain a corrosion-resistant component.

[0039] The potassium bromide tablet method was used to prepare the sample, and the modified hydroxyapatite was tested by infrared spectroscopy. Figure 1 As shown, the spectral wavenumber test range is 4000cm-1-500cm-1. Analysis shows that in the infrared spectrum of modified hydroxyapatite, 3425cm-1 is the absorption peak of hydroxyl group, 1730cm-1 is the absorption peak of carbon-oxygen double bond in ester group, 1504cm-1, 1426cm-1, 1312cm-1 are the absorption peaks of imidazole ring, and 1097cm-1 is the absorption peak of phosphate.

[0040] 2. Preparation of Strengthening Components

[0041] Step (1), heating 3.5 g of tung oil and 0.15 g of formic acid in a water bath to 60° C., stirring evenly, adding 3.5 g of 30% by mass hydrogen peroxide, reacting for 6 h, standing to separate the water layer, and distilling the oil layer under reduced pressure to obtain epoxidized tung oil;

[0042] Step (2), adding 3 g of epoxidized tung oil and 2 g of sodium lignin sulfonate to N,N-dimethylacetamide, stirring evenly, adding 0.6 g of boron trifluoride ether complex, heating to 65° C., reacting for 4 h, and distilling under reduced pressure to obtain modified sodium lignin sulfonate;

[0043] Step (3), adding 3.2 g of modified sodium lignin sulfonate into deionized water, stirring evenly, introducing nitrogen, adding 1.3 g of 3-chloropropylamine hydrochloride and 0.5 g of triethylamine, heating to 60° C., adjusting the pH value to 10, reacting for 5 h, and distilling under reduced pressure to obtain a strengthening component.

[0044] The sample was prepared by potassium bromide tablet method, and the enhanced components were tested by infrared spectrometer, such as Figure 2As shown, the spectral wavenumber test range is 4000cm-1-500cm-1. Analysis shows that in the infrared spectrum of modified sodium lignin sulfonate, 3330cm-1 is the absorption peak of hydroxyl, 1121cm-1 is the absorption peak of ether bond carbon-oxygen bond, 1039cm-1 is the absorption peak of sulfur-oxygen double bond in sulfonic acid group, and in the infrared spectrum of the enhanced component, 3428cm-1 is the absorption peak of amino group, 3335cm-1 is the absorption peak of hydroxyl group, and the peak area is reduced.

[0045] 3. Preparation of anti-corrosion coating

[0046] 80g of epoxy resin, 3g of corrosion-resistant component, 5g of reinforcing component and 1g of EFKA5065 were put into a mixer, the stirring speed was set to 600r / min, and after stirring for 2h, 15g of triethylenetetramine was added and stirred evenly to obtain an anti-corrosion coating. Example

[0047] Preparation of anti-corrosion coatings

[0048] 90g of epoxy resin, 4g of corrosion-resistant component, 6g of reinforcing component and 2g of EFKA5065 were put into a mixer, the stirring speed was set to 800r / min, and after stirring for 3h, 18g of triethylenetetramine was added and stirred evenly to obtain an anti-corrosion coating.

[0049] The preparation method of the corrosion-resistant component and the preparation method of the strengthening component are the same as those in Example 1. Example

[0050] 100g of epoxy resin, 5g of corrosion-resistant component, 7g of reinforcing component and 2g of EFKA5065 were put into a mixer, the stirring speed was set to 1000r / min, and after stirring for 4h, 19g of triethylenetetramine was added and stirred evenly to obtain an anti-corrosion coating.

[0051] The preparation method of the corrosion-resistant component and the preparation method of the strengthening component are the same as those in Example 1. Example

[0052] Preparation of anti-corrosion coatings

[0053] 100g of epoxy resin, 6g of corrosion-resistant component, 8g of reinforcing component and 3g of EFKA5065 were put into a mixer, the stirring speed was set to 1200r / min, and after stirring for 4h, 20g of triethylenetetramine was added and stirred evenly to obtain an anti-corrosion coating.

[0054] The preparation method of the corrosion-resistant component and the preparation method of the strengthening component are the same as those in Example 1.

[0055] Comparative Example 1

[0056] Coating preparation

[0057] 90 g of epoxy resin, 4 g of corrosion-resistant component and 2 g of EFKA5065 were put into a mixer, and the stirring speed was set to 800 r / min. After stirring for 3 hours, 18 g of triethylenetetramine was added and stirred evenly to obtain a coating.

[0058] The preparation method of the corrosion-resistant component is the same as that in Example 1.

[0059] Comparative Example 2

[0060] Coating preparation

[0061] 90 g of epoxy resin, 6 g of reinforcing component and 2 g of EFKA5065 were put into a mixer, and the stirring speed was set to 800 r / min. After stirring for 3 hours, 18 g of triethylenetetramine was added and stirred evenly to obtain a coating.

[0062] The preparation method of the reinforcing component is the same as that in Example 1.

[0063] Performance Testing

[0064] Performance test of the coatings prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2:

[0065] The coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were uniformly coated on tinplate, and after drying and curing, a coating was formed; the adhesion was tested according to GB / T 1720-2020; the hardness was tested according to GB / T 6739-2022, and according to the test method of GB / T 1732-2020, after being impacted by a 1 kg impact ball, the damage was observed, and the corresponding maximum impact height when the sample was not damaged was recorded to test the impact resistance; a neutral salt spray test was carried out according to GB / T 1771-1991, using 5% sodium chloride as the test solution, the test temperature was 35°C, the pH value was 7, the time was recorded, and the corrosion resistance was tested. The specific results are shown in the following table:

[0066] Adhesion grade (grade) Pencil hardness (H) Impact resistance (Kg cm) Salt spray resistance time (d)

[0067] Example 1 1 6 65 135

[0068] Example 2 1 6 75 142

[0069] Example 3 1 6 70 140

[0070] Example 4 1 6 70 141

[0071] Comparative Example 1 3 4 40 127

[0072] Comparative Example 2 2 5 50 72

[0073] It can be seen from the above table that the anti-corrosion coatings prepared in Examples 1 to 4 have excellent corrosion resistance, adhesion, hardness and impact resistance; Comparative Example 1 does not add a reinforcing component, and cannot utilize the modified sodium lignin sulfonate with an amino group to form a cross-linked network with the epoxy resin to increase the cross-linking density to improve the mechanical properties of the anti-corrosion coating, so the adhesion, pencil hardness test, and impact resistance test results are poor; Comparative Example 2 does not add a corrosion-resistant component, and cannot utilize the imidazole sustained-release component grafted on the surface of the modified hydroxyapatite to adsorb on the surface of the aluminum alloy substrate to protect the aluminum alloy substrate, and the sodium molybdate between the modified hydroxyapatite layers is released to capture corrosive anions in the environment, so the salt spray resistance test results are poor.

[0074] The anti-corrosion coating prepared in Example 1 to Example 4 is used to manufacture a corrosion-resistant aluminum alloy material. The specific manufacturing method is as follows:

[0075] After the aluminum alloy substrate is polished, cleaned and dried, the anti-corrosion coating is evenly coated on the surface of the aluminum alloy substrate. After drying and curing at 110°C for 1.5 hours, a 20 μm anti-corrosion coating is formed to obtain a corrosion-resistant aluminum alloy material for shipbuilding.

[0076] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A corrosion-resistant aluminum alloy material for shipbuilding, characterized in that: It is composed of an aluminum alloy substrate and an anti-corrosion coating coated on the surface of the aluminum alloy substrate; the anti-corrosion coating is formed by curing the anti-corrosion coating; the anti-corrosion coating comprises the following raw materials in parts by weight: 800-100 parts of epoxy resin, 15-20 parts of curing agent, 3-6 parts of corrosion-resistant component, 5-8 parts of reinforcing component, and 1-3 parts of dispersant; The method for preparing the corrosion-resistant component comprises the following steps: Step A, adding hydroxyapatite to dimethyl sulfoxide, stirring until uniformly dispersed, adding 1H-benzimidazole-5-carboxylic acid and p-toluenesulfonic acid, heating to 80-90° C., reacting for 2-3 hours, filtering, washing, and drying to obtain modified hydroxyapatite; Step B, adding modified hydroxyapatite and sodium molybdate to deionized water, introducing nitrogen, placing in a magnetic stirrer and stirring for 6-8 hours, filtering and drying to obtain a corrosion-resistant component; The preparation method of the reinforcing component comprises the following steps: Step (1), heating the tung oil and formic acid in a water bath to 50-60° C., adding hydrogen peroxide after stirring evenly, reacting for 4-6 hours, standing to separate the water layer, and distilling the oil layer under reduced pressure to obtain epoxidized tung oil; Step (2), adding epoxidized tung oil and sodium lignin sulfonate to N,N-dimethylacetamide, stirring evenly, adding boron trifluoride ether complex, heating to 60-70° C., reacting for 3-5 hours, and distilling under reduced pressure to obtain modified sodium lignin sulfonate; Step (3), adding modified sodium lignin sulfonate to deionized water, stirring evenly, introducing nitrogen, adding 3-chloropropylamine hydrochloride and triethylamine, heating to 55-65° C., adjusting the pH value, reacting for 4-6 hours, and distilling under reduced pressure to obtain a strengthening component.

2. The corrosion-resistant aluminum alloy material for shipbuilding according to claim 1, characterized in that: The preparation method of the anticorrosive coating is as follows: Put the epoxy resin, corrosion-resistant component, reinforcing component and dispersant into a mixer, set the stirring speed to 600-1200r / min, stir for 2-4h, add the curing agent, stir evenly to obtain the anti-corrosion coating.

3. The corrosion-resistant aluminum alloy material for shipbuilding according to claim 1, characterized in that: The curing agent is diethylenetriamine or triethylenetetramine; the dispersant is EFKA5065 or EFKA4010.

4. The corrosion-resistant aluminum alloy material for shipbuilding according to claim 1, characterized in that: In step A, the particle size of the hydroxyapatite is 5-8 μm.

5. The corrosion-resistant aluminum alloy material for shipbuilding according to claim 1, characterized in that: In step (1), the mass fraction of the hydrogen peroxide is 25-30%.

6. The corrosion-resistant aluminum alloy material for shipbuilding according to claim 1, characterized in that: In step (3), the pH value is adjusted to 10-10.

5.

7. A method for manufacturing a corrosion-resistant aluminum alloy material for shipbuilding as claimed in claim 1, characterized in that: As shown below: After the aluminum alloy substrate is polished, cleaned and dried, the anti-corrosion coating is evenly coated on the surface of the aluminum alloy substrate, and after drying and curing at 100-120° C. for 1-2 hours, an anti-corrosion coating is formed to obtain a corrosion-resistant aluminum alloy material.

8. The manufacturing method according to claim 7, characterized in that: The thickness of the anti-corrosion coating is 15-25 μm.

Citation Information

Patent Citations

  • Aluminum alloy anti-corrosion coatings, their preparation methods and applications

    CN106280908B

  • High-performance anti-corrosion coating for aluminum alloy and use method of high-performance anti-corrosion coating

    CN110437708A